Palaeotopography concerning sea level changes to rethink past human activities in central Dalmatian islands area, Adriatic Sea - Podobnikar, Tomaž (Acta hydrotechnica, 2018)
Environmental conditions and access to natural resources are important factors for human behaviour and choices about where to make settlements. This important information must be understood and abstracted into appropriate spatial datasets, so as to be modelled in geographic information systems (GIS). The main objective is to design and realize a seamless integrated digital elevation model (DEM) from several data sources, including bathymetry. The important focus of this paper is to collect and interpret the sea level data for the Central Dalmatian islands over the past 15,000 years, describing the entire case study%s implementation in terms of hydrology, landscape archaeology, geodesy, data quality assessment, and spatial analysis. The results demonstrate that the proposed model has the potential to rethink the archaeological theories of settlement patterns in the studied area. The limitation of the proposed study is a lower quality of bathymetric datasets, and the determination of the historical sea level due to a number of uncertain factors. The work has profound implications in terms of the developed GIS tools that make it possible to generate reliable datasets and simulate various scenarios, as well as for a non-destructive prediction of the past archaeological landscapes. The solution may help increase awareness about cultural heritage, environmental conservation, and climate change.
Keywords: bathymetric terrain model; coastline model; digital terrain model; GIS; krajinska arheologija; landscape archaeology; model obalne linije; palaeo-environment; paleookolje; prostorske analize; sea level change; spatial analyses; spreminjanje morske gladine